2020
DOI: 10.12973/eu-jer.9.3.1063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Principals’ Leadership towards Effective Learning at an Indonesian Secondary School

Abstract: <p style="text-align: justify;">The study aims to investigate the evaluation model of professional leadership and the characteristics of successful principals at an Indonesian secondary school. It is to further realize the effective learning and to produce instruments that meet the validity and reliability tests. It also aims to discover the correlation and the significance of the independent variables on the dependent variables, and the percentage of influence on the indicators in shaping the model of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…In terms of language, assessment instruments get a percentage of 87.5%. This indicates that this high order thinking skills instruments already uses language that is in accordance with the rules, easy to understand and does not give rise to double interpretation (Indra et al, 2018). This is in accordance with the opinion of Afrita & Darussyamsu (2020) that each item of the question must use clear language, easy to understand and in accordance with the enhanced spelling Judging from the high level of thinking aspects, there is an average score of 81.67 that achieves valid criteria.…”
Section: Resultssupporting
confidence: 74%
“…In terms of language, assessment instruments get a percentage of 87.5%. This indicates that this high order thinking skills instruments already uses language that is in accordance with the rules, easy to understand and does not give rise to double interpretation (Indra et al, 2018). This is in accordance with the opinion of Afrita & Darussyamsu (2020) that each item of the question must use clear language, easy to understand and in accordance with the enhanced spelling Judging from the high level of thinking aspects, there is an average score of 81.67 that achieves valid criteria.…”
Section: Resultssupporting
confidence: 74%
“…Additionally, Winter (2000) indicated that the principal of the school must demonstrate objectivity and the ability to rationalize using scientific principles. In an Indonesian study, Indra et al (2020) supported the observation that the role of a headmaster improves the professionalism of the teaching staff, thus demonstrating the importance of role implementation on the part of the school principal. Finally, Gkorezis (2016) highlighted that school principals provide leadership for empowering and enhancing the IWB of the teachers.…”
Section: Principal Support and Iwb Of Teachersmentioning
confidence: 69%
“…The idea that leadership needs to be distributed to increase the effectiveness of learning in schools is strongly supported by the principal leadership (Indra et al 2020). In achieving school improvement successful leadership is accepted.…”
Section: Figure 2 Teacher Leadership Stylesmentioning
confidence: 99%